Isolation and characterisation of cellulose from cortex, pith and whole of the Pennisetum purpureum: Effect of sodium hydroxide concentration - Tuan Rohadi, Tuan Nurain; Mohd Jamir, Mohd Ridzuan; Abdul Majid, Mohd Shukry; Sulaiman, Mohd Hafis (Elsevier B.V., 2020)
In this study, the potential of cellulose isolation from the cortex, pith, and whole of the Pennisetum purpureum stem was explored. The cellulose was extracted using 4, 8, 12, 16, and 20% concentration of alkali followed by 1.7% concentration of sodium chlorite. The cortex and pith of Pennisetum purpureum were separated using a water retting process. The thermogravimetric analysis, Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy were used to examine the thermal behaviour, composition, crystallinity, and morphological observation, respectively. The alkali treatment improved the cellulose characteristics due to the reduction of non-cellulosic materials from the cortex and pith of Pennisetum purpureum. From thermogravimetric analysis, the residues of the 8% alkali treatment for the cellulose of cortex, pith and whole of Pennisetum purpureum stems were 51.6, 61.8, and 66.45% respectively of moisture content, cellulose, hemicellulose, and lignin. The lattice transformed from cellulose I to cellulose II with concentrations of alkali treatment that exceeded 8%. Treatment with 8% alkali concentration for cellulose from the cortex produces 76.47% for the crystallinity index, which is a higher value compared to cellulose from the pith of Pennisetum purpureum.